(untitled) (Revista Direito em Debate, 2022)
The work presents a study on the destructuring of Brazilian environmental policies, especially observable during the pandemic caused by the new coronavirus, and its framing in the policies of austerity neoliberalism. Initially, aspects related to the right to an ecologically balanced environment will be addressed, enshrined in the text of the 1988 Constitution and other legal instruments. In the sequence, we present the measures of destructuring of the environmental policies implemented by the Union, during the period of the pandemic of COVID-19, as well as its consequences on the Brazilian environmental indicators. The neoliberal austerity arguments, which would justify the adoption of these measures by the Brazilian State, will be presented to demonstrate their inadequacy to the dictates enshrined in the 1988 Constitution of the Republic. Therefore, the investigation takes place through the analysis of the legislation, doctrine, and data on institutional websites and State platforms. Adopting the substantial analytical method of Prof. Washington Peluso Albino de Souza and as a theoretical reference the construction on austerity neoliberalism presented by professors Giovani Clark, Leonardo Alves Corrêa and Samuel Pontes do Nascimento.